Community-based tourism and global quality of life dynamics: A systematic review of post-pandemic research trends - Ekky Elfira Kusumawardhani (Institute for Advanced Science, Social, and Sustainable Future, 2026)
Background: The quality of life of residents in rural areas remains a central concern of sustainable development. Community-based tourism (CBT) has emerged as a widely adopted strategy for improving rural livelihoods; however, the COVID-19 pandemic has fundamentally reconfigured the economic, social, and environmental conditions within which CBT operates, necessitating a fresh synthesis of post-pandemic evidence. Methods: This systematic literature review (SLR) follows the PRISMA protocol and draws on 20 peer-reviewed articles published between 2021 and 2025, retrieved from two databases, Scopus and the Directory of Open Access Journals (DOAJ), using predefined inclusion and exclusion criteria. Thematic Narrative Synthesis was employed as the analytical framework, guided by three Research Questions addressing research trends, quality of life indicators, and critical gaps. Findings: Research activity peaked in 2023, with a predominance of quantitative methods and study locations concentrated in Asia. Economic indicators (17 studies), social indicators (15 studies), and environmental indicators (12 studies) dominated the literature. While economic and social impacts were generally reported as positive, environmental outcomes revealed persistent tensions between tourism-driven economic gains and ecological degradation, a pattern inconsistent with the Triple Bottom Line framework underpinning this review. Psychological and subjective well-being dimensions remained largely underexamined. Conclusion: Existing research remains methodologically limited, predominantly cross-sectional, and geographically concentrated, leaving critical gaps in longitudinal, comparative, and psychologically-informed approaches. Future research should integrate mixed-methods and participatory designs to capture the multidimensional nature of residents' quality of life in the post-pandemic context. Novelty/Originality of this article: This review contributes a theoretically grounded synthesis, informed by Rural Development Theory, Livelihood Theory, and Triple Bottom Line sustainability, of post-pandemic CBT research, revealing structural tensions across sustainability dimensions and proposing practical directions for community practitioners, policymakers, and development agencies to ensure equitable and holistic tourism-driven well-being.